Synthesis, photophysical and photochemical studies of benzophenone based novel monomeric and polymeric photoinitiators - Balta, Demet Karaca; Karahan, Ozlem; Avci, Duygu; Arsu, Nergis (ELSEVIER SCIENCE SA, 2015)
Four novel benzophenone-containing photoinitiators (monomers P1-1 and PI-2 and their polymers PPI-1 and PPI-2) were prepared from alkyl alpha-hydroxymethacrylates. PI-1 was synthesized from reaction of tert-butyl alpha-bromomethacrylate and 4-hydroxybenzophenone followed by cleavage of tert-butyl groups using trifluoroacetic acid. PI-2 was synthesized from reaction of ethyl alpha-bromomethacrylate and 3-benzoylbenzoic acid. Thermal polymerization of PI-1 and PI-2 was performed using 2,2'-azobis(isobutyronitrile). PI-1 and PPI-1 show UV absorption (289 and 294 nm) which are red-shifted compared to benzophenone (252 nm), PI-2 (255 nm) and PPI-2 (252 nm). All of the photoinitiators give phosphorescence emissions from their n-pi* states. The photopolymerizations of triethylene glycol dimethacrylate, 2-hydroxyethyl methacrylate and hexanediol diacrylate initiated by PI-1, PI-2, PPI-1, PPI-2 and benzophenone were studied by photo-differential scanning calorimeter using N,N-dimethyl-p-toluidine as coinitiator. Polymeric photoinitiators were found to have higher efficiencies than benzophenone and monomeric ones. Photopolymerization results are also compared to that of an alkyl alpha-hydroxymethacrylate-based photoinitiator previously reported by us; and the influence of monomer structure on polymerization efficiency is discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Photopolymerization; Benzophenone; Polymeric initiators; Methacrylate; Radical polymerization; Synthesis; SIDE-CHAIN BENZOPHENONE; COINITIATOR AMINE; CLICK REACTIONS; MAIN-CHAIN; MOIETIES; THIOXANTHONE; STATE; Chemistry; Materials Science